Відповідність параметрів обпалу окатишів різній витраті твердого палива - Бойко, Максим Миколайович; Петренко, Віталій Олександрович; Журавльова, Світлана Валеріївна (Український державний університет науки і технологій, Дніпро, 2024)
UKR: Розглянуті питання використання твердого палива для випалювання окатишів на конвеєрній машині, що дає змогу зменшити витрату природного газу на випал і поліпшити якість окатишів. Метою роботи є визначення раціонального вмісту вуглецю в окатишах для вирівнювання їх міцності до рівня, що відповідає сучасним вимогам. Даний аналіз проводився з використанням математичної моделі випалу окатишів. Встановлено, що додавання до 1% твердого палива може значно знизити перепад температур по висоті шару, що підвищує рівномірність теплової обробки окатишів. Подальше підвищення вмісту твердого палива вимагає додаткових технологічних заходів.

ENG: Questions use of solid fuel for burning pellets on a conveyor machine were considered. Its use can reduce the consumption of natural gas in the burning and improve the quality of pellets. The aim is to define rational carbon content in the pellets for alignment their strength adjustment height layer. The analysis was carried out using a mathematical model of burning pellets. The addition of up to 1% of a solid fuel can significantly reduce the temperature difference adjustment height layer. This improves the uniformity of the heat treatment of pellets. Continued increase in the content solid fuel requires additional technological measures.

ENG: Questions use of solid fuel for burning pellets on a conveyor machine were considered. Its use can reduce the consumption of natural gas in the burning and improve the quality of pellets. The aim is to define rational carbon content in the pellets for alignment their strength adjustment height layer. The analysis was carried out using a mathematical model of burning pellets. The addition of up to 1% of a solid fuel can significantly reduce the temperature difference adjustment height layer. This improves the uniformity of the heat treatment of pellets. Continued increase in the content solid fuel requires additional technological measures.
Compliance of Pellet Burning Parameters with Different Solid Fuel Consumption
М. Бойко: ORCID 0000-0003-3557-9027; В. Петренко: ORCID 0000-0001-5017-1674; С. Журавльова: ORCID 0000-0002-8519-5155
Keywords: залізорудні окатиші; теплова обробка; тверде паливо; міцність окатишів; iron ore pellets; heat treatment; solid fuel; the strength of the pellets; КМЧС; залізорудні окатиші; теплова обробка; тверде паливо; міцність окатишів; iron ore pellets; heat treatment; solid fuel; the strength of the pellets; КМЧС; TECHNOLOGY::Chemical engineering::Metallurgical process and manufacturing engineering; TECHNOLOGY::Chemical engineering::Metallurgical process and manufacturing engineering